Can we Rely on Transcutaneous Bilirbinometry during Phototherapy? (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: serum bilirubin; transcutaneous bilirubin; phototherapy; jaundice; rebound bilirubin; newborns